Anomalous Magnetic Dipole Moment \((g-2)μ\) in 3-3-1 Model with Inverse Seesaw Neutrinos - Tran Dinh, Tham; Nguyen Thanh, Phong; Le Tho, Hue (Communications in Physics, 2020)
We will show that the recent experimental value of the anomalous magnetic moment (AMM) of the charged lepton m , denoted as \(a_mu (g-2)μ/2\), can be explained successfully in a 3-3-1 model with right handed neutrino adding new heavy \(SU (3)_L\) neutrinos singlets. Allowed regions satisfying the recent AMM data are illustrated numerically.